Sertifikasi Halal di Indonesia dari Civil Society menuju Relasi Kuasa antara Negara dan Agama - Mutimmatul Faidah (Islamica: Jurnal Studi Keislaman, 2017)
This article attempts to describe the implementation of ḥalâl certification in Indonesia prior to the Law of Halal Product Assurance (Undang-Undang Jaminan Produk Halal/UU JPH), and identifies the governance of ḥalâl certification according to the law. The results of this study state that prior to the application of UU JPH, the ḥalâl certification was under the authority of Majelis Ulama Indonesia (MUI), through the Lembaga Pengkajian Pangan, Obat, dan Kosmetika (LPPOM) in the process of sertification and control product. The fatwa commission of MUI has the authority to determine the ḥalâl products and the Badan Pengawasan Obat dan Makanan (BPOM) issues the ḥalâl label. This institutional dualism makes the position of LPPOM weak. The organization does not have the authority to force manufacturers to certify, because the halal certification is voluntary, not mandatory. Similarly, the function of oversight and enforcement was weak because there is no legal provision which obliges company to certify its product. In addition, the UU JPH removes the dualism of ḥalâl certification institutions under the authority of the Ministry of Religious Affairs. The fusion of ḥalâl certification system provides the legal basis for the ḥalâl certification obligations for products and firmness in the monitoring and surveillance systems of ḥalâl products.